Acoustic Vulnerability, Hydraulic Capacitance, and Xylem Anatomy Determine Drought Response of Small Grain Cereals - Degraeve, Szanne; De Baerdemaeker, Niels J. F.; Ameye, Maarten; Leroux, Olivier; Haesaert, Geert Jozej Willem; Steppe, Kathy (Frontiers in Plant Science, 2021)
Selection of high-yielding traits in cereal plants led to a continuous increase in productivity. However, less effort was made to select on adaptive traits, favorable in adverse and harsh environments. Under current climate change conditions and the knowledge that cereals are staple foods for people worldwide, it is highly important to shift focus to the selection of traits related to drought tolerance, and to evaluate new tools for efficient selection. Here, we explore the possibility to use vulnerability to drought-induced xylem embolism of wheat cultivars Excalibur and Hartog (Triticum aestivum L.), rye cultivar Duiker Max (Secale cereale L.) and triticale cultivars Dublet and US2014 (x Triticosecale Wittmack) as a proxy for their drought tolerance. Multiple techniques were combined to underpin this hypothesis. During bench-top dehydration experiments, acoustic emissions (AE) produced by formation of air emboli were detected, and hydraulic capacitances quantified. By only looking at the AE50 values, one would classify wheat cultivar Excalibur as most tolerant and triticale cultivar Dublet as most vulnerable to drought-induced xylem embolism. Though, Dublet had significantly higher hydraulic capacitances, which are essential in terms of internal water storage to temporarily buffer or delay water shortage. In addition, xylem anatomical traits revealed that both cultivars have a contrasting trade-off between hydraulic safety and efficiency. This paper emphasizes the importance of including a cultivar’s hydraulic capacitance when evaluating its drought response and vulnerability to drought-induced xylem embolism, instead of relying on the AE50 as the one parameter.